Growth Mindset dan Efikasi Diri Akademik pada Mahasiswa - Dhimas Arya Wahyukencana; Narastri Insan Utami (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This research aims to determine the relationship between growth mindset and academic self-efficacy in students. The hypothesis in this research is that a positive relationship exists between growth mindset and academic self-efficacy in students. This research method uses quantitative research. The type of research used is descriptive. The primary data source used is students. The data collection technique uses a questionnaire with a Likert scale. The data analysis used a correlation between variables. The research results obtained a correlation coefficient (rxy) = 0.507 (p = 0.000), meaning a positive relationship exists between growth mindset and academic self-efficacy in students. The coefficient of determination (R2) is 0.257, which shows that work enthusiasm contributes to work discipline only 25.7%. At the same time, the rest is influenced by other factors not examined in this research.